Lenticulostriate vasculopathy in routine brain ultrasonography in infants: next step? - Suada Heljić; Hajrija Maksić; Sabina Terzic (Medicinski glasnik, 2022)
Lenticulostriate vasculopathy (LSV) is a relatively common fi nding in routine cranial ultrasound examination that has been associated with many infectious and non-infectious conditions. The aim of this review was to provide a better understanding of LSV ultrasound fi nding, as well as the need for further laboratory and imaging examinations in infants. The most of the published studies represented small series, with few prospective long-term studies involving the control groups. Authors have mostly found an association between LSV, especially higher-grade (although there is no universally accepted classifi cation) with congenital cytomegalovirus (CMV) infection, classifying those children as at risk for sensorineural hearing loss. In contrast, some authors pointed out that LSV could be found relatively often, and believe that isolated LSV, especially lower-grade, is not predictive for an unfavourable outcome and a long-term prognosis. Therefore, although 35 years have passed since the fi rst publication of LSV, there is still no consensus among experts on the clinical signifi cance of isolated LSV, but caution is certainly needed given the fact that most infants with congenital CMV are asymptomatic.
Keywords: brain ultrasonography; cytomegalovirus; lenticulostriate vasculopathy; newborn lenticulostriate vasculopathy